Effects of sleep deprivation on different phases of memory in the rat: dissociation between contextual and tone fear conditioning tasks - Rossi, Vanessa Contatto; Tiba, Paula Ayako; Moreira, Karin Di Monteiro; Ferreira, Tatiana Lima; Oliveira, Maria Gabriela Menezes; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2014)
Numerous studies show that sleep deprivation (SD) impacts negatively on cognitive processes, including learning and memory. Memory formation encompasses distinct phases of which acquisition, consolidation and retrieval are better known. Previous studies with pre-training SD induced by the platform method have shown impairment in fear conditioning tasks. Nonetheless, pre-training manipulations do not allow the distinction between effects on acquisition and/or consolidation, interfering, ultimately, on recall of/performance in the task. In the present study, animals were first trained in contextual and tone fear conditioning tasks and then submitted to SD with the purpose to evaluate the effect of this manipulation on different stages of the learning process, e.g. in the uptake of (new) information during learning, its encoding and stabilization, and the recall of stored memories. Besides, we also investigated the effect of SD in the extinction of fear memory and a possible state-dependent learning induced by this manipulation. For each task (contextual or tone fear conditioning), animals were trained and then distributed into control, not sleep-deprived (CTL) and SD groups, the latter being submitted to the modified multiple platform paradigm for 96 h. Subsets of eight rats in each group/experiment were submitted to the test of the tasks, either immediately or at different time intervals after SD. The results indicated that a) pre-, but not post-training SD impaired recall in the contextual and tone fear conditioning; b) this impairment was not state-dependent; c) in the contextual fear conditioning, pre-test SD prevented extinction of the learned task. Overall, these results suggest that SD interferes with acquisition, recall and extinction, but not necessarily with consolidation of emotional memory.